Vordenker wider Willen. Der dogmatische Standpunkt Magnús Eiríkssons - Schreiber, Gerhard (Zeitschrift für neuere Theologiegeschichte, 2024)
The article focuses on the Icelandic theologian Magnús Eiríksson (1806-1881), whose extensive writings have hitherto been a blind spot in research. The life and authorship of this controversial and independent thinker from the Golden Age of Denmark are sketched out with constant attention to his dogmatic stance, and key themes and motifs of his thought are explored with the aim of theological-historical contextualization. Remarkable similarities are found with the interpretation of the history of Christianity as a process of alienation, later prominently represented by Adolf von Harnack, while Eiríksson also proves to be a forward-looking theologian in other respects, making an in-depth study of his work both rewarding and profitable.